FINE STRUCTURE IN THE INFRARED OH-STRETCHING BANDS OF HOLMQUISTITE AND ANTHOPHYLLITE - Ishida K.; Hawthorne F.C. (My University, 2003)
The principal infrared OH-stretching bands in the orthorhombic (Mg, Fe, Mn, Li) amphiboles holmquistite and anthophyllite show fine structure due to the occurrence of two symmetrically distinct OH groups in the crystal structure. There are two distinct tetrahedral double chains in the orthorhombic amphibole structure, the A chain and the B chain. The B chain is more rotated than the A chain, and the stereochemistry around each of the OH sites suggests that the hydrogen bond to the bridging anion(s) of the B chain is stronger than the hydrogen bond to the bridging anion(s) of the A chain. This difference is sufficient to shift the frequency of the principal OH2-stretching band(s) ~5 cm-1 to lower frequency, and allows resolution of the two bands in the infrared spectrum. This distinction could allow detection of possible OH, F ordering between the two distinct monovalent-anion sites in the orthorhombic amphibole structure.
Keywords: FTIR; OH-STRETCHING BAND; FINE STRUCTURE; ORTHORHOMBIC MG-FE-MN-LI AMPHIBOLES; HOLMQUISTITE; ANTHOPHYLLITE